A New Estimation of the Growth Bound of a Periodic Evolution Family on Banach Spaces - Constantin Buse; Aftab Khan; Gul Rahmat; Afshan Tabassum (Journal of Function Spaces and Applications, 2013)
Let be a strongly continuous and -periodic evolution family acting on a complex Banach space . We prove that if and then the growth bound of the family is less than or equal to .